Dinamika Sosial Warga Di Kawasan Permukiman Baru: Perumahan Gria Mahakam City, Kecamatan Sungai Kunjang, Kota Samarinda - Ahid Yusuf Hidayat; Juwari Juwari; Iya' Setyasih; Sutriani Sutriani (Universitas Medan Area, 2026)
This study aims to analyze the social dynamics of residents in the new housing complex of Gria Mahakam City, Samarinda. The focus of this study is on how social interaction, social participation, social capital, and social barriers are formed within a modern housing environment. To address this issue, the study draws upon Blumer’s theory of symbolic interactionism, Putnam’s theory of social capital, and Giddens’ theory of modernity. Data were collected through in-depth interviews, participant observation, and documentation from 30 informants selected through purposive sampling, and were then analyzed qualitatively through data reduction, presentation, and drawing of conclusions. This study concludes that the social dynamics of residents are in a transitional phase toward more stable social cohesion, where social interaction remains limited, participation is fluctuating, and social capital is beginning to develop but is not yet evenly distributed. Social barriers are influenced by individual and structural factors, while contextually, these dynamics are linked to Samarinda’s position as a developing city and a buffer zone for the Nusantara Capital City, meaning that community formation occurs gradually and is influenced by residents’ characteristics as well as regional development.